Model Matematika Pengaruh Lingkungan Terhadap Dinamika Jumlah Populasi Pejudi - Rozi Wahyudi; Media Rosha; Riry Sriningsih (UNIVERSITAS NEGERI PADANG, 2021)
Abstract – The article discussed mathematical model of the environmental influences to dynamics of gambler population. This research was started with forming mathematical model of the environmental influences to dynamics of gambler population in non-linear differential equations system. Based on analysis model, there are two types of equilibrium point that are free equilibrium point of gambler and endemic equilibrium point. Existence and stability of the equilibrium points are determined by the basic reproduction number. By analyzing the model, obtained the stability of each equilibrium points.Keywords – mathematical model, gambler, equilibrium, stability, basic reproductive number